Inhibiting Factors in Library Management Affecting Students’ Reading Interest at SMPN 09 Tulang Bawang Barat - Sabrina Bintang Amalia Tusyifa; Rizka Pitri; Reza Nawafella Alya Parangu (Jurnal El-Pustaka, 2025)
School libraries play an important role in supporting the teaching and learning process and fostering students' interest in reading. However, observations at SMPN 09 Tulang Bawang Barat show that students' interest in reading is still low despite the relatively large book collection and library facilities. This study aims to identify inhibiting factors in library management that impact students' interest in reading. The research method used is a mixed method, with a quantitative and qualitative approach. Quantitative data were obtained through questionnaires distributed to 64 eighth-grade students, while qualitative data were obtained through interviews, observations, and documentation with the head of the library. The results showed that inhibiting factors in library management on students' interest in reading at SMPN 09 Tulang Bawang Barat include various obstacles such as budget constraints, shortage of personnel, a very limited number of library staff and inadequate facilities and technology, lack of supporting facilities, and outdated book collections. These conditions lead to low student enthusiasm for visiting and reading in the library.